Ensuring Human Rights in Ukraine: Problematic Issues and Ways of their Solution in the Social and Legal Sphere - Leheza, Yevhen; Filipenko, Tatiana; Sokolenko, Olha; Darahan, Valerii; Kucherenko, Oleksii (Cuestiones Políticas, 2020)
The article discusses some complex factors influencing the process of realization of human rights in Ukraine, highlights the unified approach to the classification of legal norms that exercise human rights and freedoms, as well as problems and development prospects. Now the real protection of human rights is one of the most acute problems of the Ukrainian reality. It serves as one of the most important tasks, not only for the functioning but also for the existence of the Ukrainian state. Therefore, it should be borne in mind that guaranteeing respect for human rights in Ukraine is only possible through effective reform of the power system and compliance with an integrated approach to guarantee human rights, both by the State and by society. civil. It is concluded that guaranteeing the general enjoyment and enjoyment of human rights is a matter of co-responsibilities, which is why it is also negatively affected by the rigid opposition of the political forces, which undermines the stability of society, the stability of the constitutional order. , while increasing the low level of legal culture of officials and citizens.